Pelatihan Budidaya Maggot untuk Meningkatkan Ketrampilan Masyarakat dalam Pengolahan Limbah Organik Rumah Tangga dan Menciptakan Peluang Usaha di Kelurahan Umbulmartani, Ngemplak, Sleman - Octavia, Bernadetta; Rakhmawati, Anna; Aminatun, Tien; Suhartini, Suhartini; Aulia, Fera (Yogyakarta State University, 2025)
The accumulation of rubbish at temporary waste storage locations has become a common concern for us. The organic waste in the rubbish pile usually causes a very strong pungent odor. In fact, if organic waste is managed from every house/location that produces it, it will very significantly reduce both the volume of rubbish piles and the pungent stench. Therefore, it is necessary to instill awareness in every member of society about the importance of managing waste and specifically organic waste which can be degraded by various types of organisms. One of the organisms that can be used to process this organic waste is maggot, which is the larva of the black soldier fly (BSF). Apart from being an organic waste processing agent, maggots can also be used as a feed supplement for chickens and fish. In this way, maggot cultivation can have a dual function for community members who are motivated to manage organic waste independently. Through Lecturer Activities Off Campus (DLK) activities this year, the community in Umbulmartani Village, Ngemplak District, Sleman was given training on Maggot Cultivation to be used as an organic waste processor on a household scale and can also be used to improve the family economy if maggot cultivation is carried out managed seriously. The final activity is evaluation. The program results show the success of the process as indicated by: a. Attendance of participants reaches 100%, b. Increasing knowledge and skills in cultivating maggots for processing family organic waste, c. The results of the participant satisfaction questionnaire showed that participant satisfaction in all aspects was good and very good.